2006
DOI: 10.1002/jez.b.21117
|View full text |Cite
|
Sign up to set email alerts
|

Lectin‐binding pattern as tool to identify and enrich specific primary testis cells of the tilapia (Oreochromis niloticus) and medaka (Oryzias latipes)

Abstract: Cell type-specific lectin binding is a useful tool for the analysis of developing systems. We describe the binding pattern of 21 different fluorescein isothiocyanate (FITC)-labelled lectins to the testis of two model teleost species, the medaka (Oryzias latipes) and the tilapia (Oreochromis niloticus). The analysis of the binding pattern was carried out on tissue sections (medaka and tilapia) and using primary culture cells (only tilapia). Lectin binding was studied by confocal microscopy and for histological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 33 publications
0
8
0
2
Order By: Relevance
“…On one hand, genes encoding immune-related proteins also encode hormone receptor-related proteins. A large number of immune-related proteins, such as lectins37, lysozyme, hepcidin and complement components3839, including ERα, have been identified in fish gonads. Massartr found that ERα was expressed in the immune organs of O. mykis s40.…”
Section: Discussionmentioning
confidence: 99%
“…On one hand, genes encoding immune-related proteins also encode hormone receptor-related proteins. A large number of immune-related proteins, such as lectins37, lysozyme, hepcidin and complement components3839, including ERα, have been identified in fish gonads. Massartr found that ERα was expressed in the immune organs of O. mykis s40.…”
Section: Discussionmentioning
confidence: 99%
“…A number of the genes that encode for immune proteins are co-expressed with those that encode for sex-steroid receptors. For example, lectins (Tokalov and Gutzeit 2007;Swain and Kayak 2009), lysozyme, hepcidin and complement component 3 (Saurabh and Sahoo 2008;Chaves-Pozo et al 2008), Toll-like receptors and interleukins (Kumari et al 2009;Yu et al 2009) are abundantly found in the gonadal tissues. Conversely, ER and AR are widely distributed in immune tissues, such as the spleen, liver, and anterior kidney leukocytes (Slater et al 1995;Todo et al 1999;Lynn et al 2008;Liu et al 2009;Shved et al 2009), suggesting these organs may be targets for sex-steroids.…”
Section: Interactions Between the Reproductive And Immune Systems In mentioning
confidence: 99%
“…4). In non‐transgenic cultures, different cell populations can be recognized by forward scatter (FSC) analysis (Tokalov and Gutzeit, 2007) in which the smallest cells with low FSC can be recognized as spermatids (St) and spermatozoa (Sz). The large spermatogonia, characterized by high FSC, exhibit the strongest fluorescence in oct4 ‐EGFP fish and comprise 1–3% of all primary testis cells (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Primary testis cells of oct4 ‐EGFP transgenic medaka and non‐transgenic medaka were isolated as described (Tokalov and Gutzeit, 2007) without Percoll gradient centrifugation. To determine their DNA content, cells were stained with Hoechst 33342 (5 µg/ml; Life Technologies) for 30 min, washed once, and kept in DMEM (Biochrom, Germany) supplemented with 2% fetal calf serum (PAA, Austria).…”
Section: Methodsmentioning
confidence: 99%